Tantangan Hukum Dalam Menyikapi Perceraian Tanpa Sidang Di Era Digital - Delisa, Apifah; Fuad Rahman; Siti Marlina; Madyan (Institut Muslim Cendekia, 2025)
The development of information technology in the digital era has influenced various aspects of life, including in the resolution of divorce cases. One phenomenon that has emerged is divorce without going through a court hearing, which is widely chosen because it is considered faster, more practical, and more efficient. However, this practice raises various legal issues, such as the unclear legal status of the couple, the unprotected rights of women and children, and the potential for violations of the principles of justice and legal certainty. This study aims to examine and analyze the legal challenges arising from the practice of divorce without a trial in the digital era and to provide constructive recommendations to overcome them. The method used in this study is a qualitative method with a normative approach through literature studies of regulations, legal doctrines, and case studies in Indonesia. The results of the study show that the absence of clear regulations regarding online mediation, weak legal literacy of the community, and limited access to the digital justice system are the main obstacles in responding to this phenomenon. The conclusion of this study emphasizes the need for regulatory updates, integration of technology with the legal system, and strengthening digital legal literacy and ethics so that divorce in the digital era remains within the corridor of legitimate and just law.